PREVALENCE OF GENOTYPES IN HELICOBACTER PYLORI ISOLATES FROM PATIENTS IN EASTERN TURKEY AND THE ASSOCIATION OF THESE GENOTYPES WITH CLINICAL OUTCOME - Ozbey, Gokben; Aygun, Cem (Springer, 2012)
There is not much information available regarding the prevalence of the genotypes of Helicobacter pylori isolates in Turkey, particularly in eastern Turkey. The aims of this study were to detect the prevalence of different genotypes of H. pylori in Turkish patients with gastrointestinal complaints and to determine the relationship of these genotypes with clinical outcome and sex. One hundred forty H. pylori isolates were examined for the presence of its genotypes by the PCR. We found that the prevalence of vacAs1, vacAs2, cagA, cagE, iceA1, iceA2 and babA2 genes were 88.6%, 11.4%, 71.4%, 35.7%, 41.4%, 58.6%, and 62.1%, respectively. The most predominant vacA subtype was s1a (81.4%). The most vacA allelic combination detected were vacAs1m1 (65.2%) and s1m2 (53.9%) in patients with peptic ulcer and gastritis, respectively. The only vacAs1 isolate was significantly associated with gastritis and peptic ulcer (p<0.05). The vacAs1a, ml, slml and babA2 genes were significantly associated with peptic ulcer (p<0.05), whereas m2 gene was significantly associated with only gastritis (p<0.05). The difference between sex and genotypes was statistically significant among the cagA, vacAs1, iceA2 and babA2 genes. This study reported for the first time the prevalence of H. pylori genotypes in patients with gastrointestinal complaints in eastern Turkey. Further studies are needed to understand epidemiological importance of the genotypes of H. pylori isolates in this region and the association between the virulence genes and clinical outcome in different regions.
Keywords: Helicobacter pylori; prevalence; patient; genotypes; PCR